The Effective Use Of Videos In Sociology Courses - Piker-King, Kathleen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
I use both educational and popular videos in all the sociology courses that I teach. These courses range from the introductory level to the upper division level. Instructional scaffolding consists of teaching specific theoretical and/or empirical material before showing the videos, then students are given the opportunity to build their understanding of the theoretical and/or empirical material by viewing the videos and applying the information from the previous lectures to the video presentation. The viewing guides are used as templates for achieving scaffolding.